Histamine receptors and cancer pharmacology - Medina, Vanina Araceli (2010)
Considerable evidence has been collected indicating that histamine can modulate proliferation of different normal and malignant cells. High histamine biosynthesis and content together with histamine receptors have been reported in different human neoplasias including melanoma, colon and breast cancer, as well as in experimental tumours in which histamine has been postulated to behave as an important paracrine and autocrine regulator of proliferation. The discovery of the human histamine H(4) receptor in different tissues has contributed to our understanding of histamine role in numerous physiological and pathological conditions revealing novel functions for histamine and opening new perspectives in histamine pharmacology research. In the present review we aimed to briefly summarize current knowledge on histamine and histamine receptor involvement in cancer before focusing on some recent evidence supporting the novel role of histamine H(4) receptor in cancer progression representing a promising molecular target and avenue for cancer drug development.